The effects of a training program based on the health promotion model on physical activity in women with type 2 diabetes: A randomized controlled clinical trial - Soghra Rouholamini; Mahin Gheibizadeh; Elham Maraghi; Alireza Jahanshahi (Wolters Kluwer Medknow Publications, 2020)
Background: Physical activity among women with type 2 Diabetes Mellitus (DM) is an undesirable level. This study aimed to determine the effect of a training program based on the Health Promotion Model (HPM) on physical activity in women with type 2 DM. Materials and Methods: This randomized clinical trial was performed on 128 women with type 2 DM, who were randomly assigned to control and intervention groups. Data were collected using the Baecke Physical Activity Questionnaire (BPAQ) and a researcher-made questionnaire designed based on the HPM constructs before and 2 months after the intervention. The training was carried out in four sessions in the intervention group and the control group received regular education at the clinic. Data were analyzed using Chi-square, Fisher's exact test, paired t-test, independent t-test, and Mann-Whitney and Wilcoxon tests in Statistical Package for the Social Sciences (SPSS) software. Results: The findings showed that the mean [Standard Deviation (SD)] of physical activity in the intervention and control groups before the intervention was 6.52 (0.86) and 6.56 (1.07), respectively, and there was no significant difference between the groups (p = 0.95). However, after the intervention, the mean (SD) of physical activity in the intervention and control groups was 8.04 (0.92) and 6.33 (1.60), respectively, which showed a significant difference (t126 =9.71,p < 0.001). Conclusions: The findings of this study revealed that the training program based on the HPM has a positive effect on improving physical activity in women with type 2 DM.